Anonymous communication in overlay networks. Issue 3 (29th March 2012) - Ren, Jian; Li, Yun; Jiang, Tingting; Li, Tongtong
Abstract: Communication anonymity is becoming an increasingly important, or even indispensable, security requirement for many applications. The existing research in anonymous communications can largely be divided into two categories: mix‐based systems and secure multiparty computation‐based systems, originating from mixnet and DC‐net, respectively. However, they either cannot provide provable anonymity or suffer from transmission collision problem. In this paper, we first propose a novel unconditionally secure source anonymous message authentication code that can be applied to any messages without relying on any trusted third parties. While ensuring message sender anonymity, secure source anonymous message authentication code can also provide message content authenticity. We then propose a novel communication protocol that can hide the senders and the recipients from each other and thus can be used for secure file sharing. The security analysis demonstrates that the proposed protocol is secure against various attacks. Our analysis also shows that it is efficient and practical. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : We first propose a novel unconditionally secure source anonymous message authentication code that, while ensuring message sender anonymity, can also provide message content authenticity. We then propose a novel and practical communication protocol to hide the senders and the recipients from each other. The security analysis demonstrates that the proposed protocol is secure against various attacks.